Dynamic behaviour of flow through three circular cylinders in staggered arrangement with three disturbance bodies around the upstream cylinder / Sutardi Banta Cut and Wawan Aries Widodo - Banta Cut, Sutardi; Widodo, Wawan Aries (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2023)
Studies on flow through cylinders have been widely carried out, both experimentally and numerically. The purpose of those studies is to obtain information about flow phenomena around the cylinder arrangement, such as aerodynamic forces, vortex shedding, and vortex-induced vibration. This study aims to evaluate the flow characteristics that pass through three circular cylinders arranged in a stagger and reduce the drag force (CD) by adding 3 disturbance bodies (DB) around the upstream cylinder.